Analysis Of The Transformation Of Middle Eastern Graduates Of Islamic Scholars In The Renewal Of Islamic Thought And Islamic Boarding School Education In Indonesia (20th-21st Century) - Ningrum, Melisa Putri Dwi; Amin, Alfauzan; Saepudin, Saepudin (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
As a means of cultivating ideals in social life and within formal settings, Islamic education in the Indonesian archipelago has been a long process of transforming Islamic principles. The goal of this curriculum is to shape complete human beings, whole in spirit, mind, and community—a goal that goes beyond simply transferring knowledge. Local institutions such as halaqah (Islamic spiritual circles), meunasah (Islamic boarding schools), and pesantren (Islamic educational schools) have evolved to meet the needs of Muslims throughout history, beginning with marriage, trade, and da’wah (Islamic outreach). Indonesia’s oldest cultural institution, the pesantren, played a crucial role in da’wah, the development of ulama (Islamic scholars), and the struggle for independence. The presence of ulama and the Islamic da’wah process, or rihlah ilmiyah (Islamic outreach), also helped ensure the continued development of Islamic scholarship throughout the Indonesian archipelago. The colonial era, which prohibited Islamic education, was only one of many obstacles that Islamic schools had to overcome. However, it also sparked many new ideas, such as how to combine religious and secular education in Islamic madrasas. The transition from IAIN to UIN is just one example of how Islamic education has adapted to the contemporary global era through digitalization, curriculum reform, and institutional change. Islamic education in Indonesia is an effective system for producing moderate, character-based, and internationally competitive Muslims because it is both traditional and adaptive.